2013
DOI: 10.4048/jbc.2013.16.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic Sarcoma in Breast after Bone Marrow Transplantation

Abstract: Granulocytic sarcoma is a localized extramedullary solid tumor composed of immature myeloid cell and is usually associated with acute myeloid leukemia or myelodysplastic syndrome. Although it can involve any site, commonly in lymph nodes, skin, bone and soft tissue, the involvement of breast is unusual. Especially, the involvement of the breast as a pattern of relapse after bone marrow transplantation is extremely rare. We have experienced 2 cases of granulocytic sarcoma after bone marrow transplantation. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Granulocytic sarcoma relapse following allo-HSCT of AML is extremely rare[ 7 ]. A European retrospective analysis reported that GS occurred 4-56 mo after HSCT in less than 1% of transplanted patients[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Granulocytic sarcoma relapse following allo-HSCT of AML is extremely rare[ 7 ]. A European retrospective analysis reported that GS occurred 4-56 mo after HSCT in less than 1% of transplanted patients[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid sarcoma is also known as granulocytic sarcoma, monocytic sarcoma, extramedullary myeloid cell tumor, myeloblastoma, and chloroma [1]. The term “chloroma” was initially adopted owing to the greenish color assumed by the tumor cells on myeloperoxidase staining [1]; the term is currently not in use because not all tumor cells assumed a greenish color on staining [14].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid sarcoma can affect any part of the body, and the most commonly affected sites are the lymph nodes, skin, bones, central nervous system, and soft tissue [14]. Breast involvement is rarely observed in myeloid sarcoma [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid sarcoma, also known as extramedullary myeloid cell tumor, myeloblastoma or chloroma, is a rare, solid extramedullary tumor originating from immature granulocytic cells or monocytes. It frequently invades the bone, soft tissues, lymph nodes, skin, and paranasal sinuses [ 1 2 3 ]. Myeloid sarcoma, which can be seen in 2–14% of acute myeloid leukemia (AML) patients, is mostly seen together with chronic myeloid leukemia or myelodysplastic syndromes [ 1 2 3 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It frequently invades the bone, soft tissues, lymph nodes, skin, and paranasal sinuses [ 1 2 3 ]. Myeloid sarcoma, which can be seen in 2–14% of acute myeloid leukemia (AML) patients, is mostly seen together with chronic myeloid leukemia or myelodysplastic syndromes [ 1 2 3 4 5 ]. Breast involvement without an aleukemic or myeloproliferative disorder is extremely rare [ 3 4 6 7 8 9 ].…”
Section: Introductionmentioning
confidence: 99%